Association between social capital and self-rated health among community-dwelling older adults - Bai, Zhongliang; Yang, Jing; Wang, Zijing; Cao, Wenwen; Cao, Chenglin; Hu, Zhi; Chen, Ren (Frontiers in Public Health, 2022)
Background It is less known about whether the association of social capital with self-rated health (SRH) varies by the presence of health conditions and how social capital, together with other variables, is linked to self-rated health in later life. Objectives This article aimed to explore the association of social capital with self-rated health and to examine whether the association varies among older people with and without health conditions, with a special focus on how social capital and relevant factors have an effect on self-rated health among community-dwelling older adults. Methods Cross-sectional data were obtained from a survey that commenced from July to September 2017 in Anhui Province. Data on socio-demographic information, social capital (six dimensions), and self-rated health were analyzed. Binary logistic regression and classification and regression tree (CART) models were used to estimate the association. Results Based on the findings, we found that social capital regarding less social support (adjusted odds ratio (AOR) = 1.57, 95% CI: 1.21–2.04), and less reciprocity (AOR = 1.73, 95% CI: 1.29–2.31) were associated with self-rated health among general older adults. Social capital as measured by less social participation (AOR = 1.55, 95% CI: 1.06–2.27), less cohesion (AOR = 0.63, 95% CI: 0.42–0.94), and less reciprocity (AOR =1.77, 95% CI: 1.17–2.68) were linked to self-rated health among older people with health conditions. While social capital regarding less social support (AOR = 2.15, 95% CI: 1.39–3.33) was related to self-rated health among older people without health conditions. We observed the interacting effect of social capital in the CART model, an implication that much focus should be geared toward vulnerable subgroups, especially depressed and lonely older people, as they have low reciprocity and little cohesion. Conclusion This work demonstrates that social capital may be relevant in devising programs and measures to improve self-rated health among community-dwelling older adults with comorbidity.